THE USE OF SPEECH ACT IN ONLINE NEWSPAPER: A CASE STUDY OF DETIK.COM - Rahma Indriyani; Purba, Siti Rahmah; Pulungan, Anni Holila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the realization of Speech Acts within online news media, specifically focusing on articles published in the Law and Criminal section of Detik.com, one of Indonesia’s most popular news portals. Drawing on the Speech Act Theory introduced by J.L. Austin (1962) and further developed by John Searle (1969), the research explores how language in online journalism functions not merely as a tool for reporting facts, but as a mechanism for performing actions such as persuading readers, framing social issues, and constructing public opinion. Using a qualitative descriptive design, the study analyzed utterances, statements, and quotations sourced from legal authorities, victims, and suspects in Detik.com articles published between January and October 2025. The findings indicate that assertive/representative speech acts dominate the reporting in the Law and Criminal section. These acts are primarily employed by authoritative sources, such as the police, to provide factual, objective, and instructive accounts of events, thereby shaping the meaning of the case for the public. Furthermore, the study identified the presence of Commissives (used by officials to commit to future actions or disclosures) and Expressives (used by individuals to convey psychological states like relief or shock). This research fills a gap by demonstrating that Detik.com journalists actively perform linguistic actions that construct public trust and shape moral judgments, highlighting how linguistic choices reflect broader social and legal ideologies within institutional discourse.